IMPLICATIONS OF MEDICAL BASED RECORDS ON HEALTHCARE DELIVERY IN BAMENDA HEALTH DISTRICT, CAMEROON - Tambi, Mbu Daniel (Economic Review: Journal of Economics and Business, 2025)
This study has as objectives: to examine the effect of well-preserved medical based records on healthcare service delivery, to verify the heterogeneity effect of medical based records on healthcare service delivery by the type of medical record, and to determine the challenges associated with the keeping of medical records in Bamenda Health District, Cameroon. The marginal effect estimate of the probit model is used to estimate the result, while primary data was collected among 267 health personnel. The result shows that well-preserved medical based records strongly correlate with quality healthcare service delivery, and it is a paper-electronic based phenomenon. The challenges faced in the process of keeping medical records are: shortage of filing space, misfiling and missing files, damage to records, incompetent/unskilled staff, shortage of staff, lack of support for resources, and insufficient budget. The study suggests that: (1) decision makers should valorize the keeping of medical records as it enhances quality healthcare service delivery; (2) the health sector should include record keeping in the training curriculum of personnel and (3) more awareness should be made regarding record keeping by the actors. All these are good steps toward better health service.